Source of Wisdom : Old English & Early Medieval Latin Studies in Honour of Thomas D. Hill - Hall, Thomas N.; Biggs, Frederick M.; Wright, Charles Darwin, 1954-; Hill, Thomas D., 1940- (Book collections on Project MUSE., 2007)
As one of the most prolific and influential scholars in the field, Thomas D. Hill has made an indelible mark on the study of Old English literature. In celebration of his distinguished career, the editors of Source of Wisdom have assembled a wide-ranging collection of nineteen original essays on Old English poetry and prose as well as early medieval Latin, touching upon many of Hill?s specific research interests. Among the topics examined in this volume are the Christian-Latin sources of Old English texts, including religious and?sapiential? poetry, and prose translations of Latin writings. Old English poems such as Beowulf, The Dream of the Rood, and The Wife?s Lament are treated, throughout, to thematic, textual, stylistic, lexical, and source analysis. Prose writers of the period such as King Alfred and Waerferth, as well as medieval Latin writers such as Bede and Pseudo-Methodius are also discussed. As an added feature, the volume includes a bibliography of publications by Thomas D. Hill. Source of Wisdom is, ultimately, a contribution to the understanding of medieval English literature and the textual traditions that contributed to its development.